Safeguarding Intangible Cultural Heritage: traditional foodways of the East Pokot community of Kenya - Maundu, P.; Kapeta, B.; Muiruri, P.; Morimoto, Y.; Bosibori, E.; Kibet, S.; Odubo, A.; UNESCO Safeguarding Intangible Cultural Heritage (UNESCO, 2013)
This document presents the results of documentation of traditional foodways conducted in the East Pokot community of Kenya within the project ‘Safeguarding traditional foodways of two communities in Kenya. The documentation was undertaken between 2010-2012 largely by pupils of two primary schools - Chemolingot and Churo assisted by their teachers, a local project coordinator and the project team mainly consisting of staff from National Museums of Kenya, Bioversity International and the Department of Culture.